Low-Cytotoxic Synthetic Bromorutaecarpine Exhibits Anti-Inflammation and Activation of Transient Receptor Potential Vanilloid Type 1 Activities. (28th November 2013) - Lee, Chi-Ming; Gu, Jiun-An; Rau, Tin-Gan; Yang, Che-Hsiung; Yang, Wei-Chi; Huang, Shih-Hao; Lin, Feng-Yen; Lin, Chun-Mao; Huang, Sheng-Tung
Abstract : Rutaecarpine (RUT), the major bioactive ingredient isolated from the Chinese herb Evodia rutaecarpa, possesses a wide spectrum of biological activities, including anti-inflammation and preventing cardiovascular diseases. However, its high cytotoxicity hampers pharmaceutical development. We designed and synthesized a derivative of RUT, bromo-dimethoxyrutaecarpine (Br-RUT), which showed no cytotoxicity at 20  μ M. Br-RUT suppressed nitric oxide (NO) production and tumor necrosis factor- α release in concentration-dependent (0 ~ 20  μ M) manners in lipopolysaccharide (LPS)-treated RAW 264.7 macrophages; protein levels of inducible NO synthase (iNOS) and cyclooxygenase-2 induced by LPS were downregulated. Br-RUT inhibited cell migration and invasion of ovarian carcinoma A2780 cells with 0 ~ 48 h of treatment. Furthermore, Br-RUT enhanced the expression of transient receptor potential vanilloid type 1 and activated endothelial NOS in human aortic endothelial cells. These results suggest that the synthetic Br-RUT possesses very low cytotoxicity but retains its activities against inflammation and vasodilation that could be beneficial for cardiovascular disease therapeutics.